ISRAEL PALESTINE CONFLICT AND INDIAN DIPLOMACY-AN EMPIRICAL STUDY (International Journal of Food and Nutritional Sciences, 2019)
The Israel-Palestine conflict is a complex geopolitical issue with historical roots. The conflictprimarily revolves around competing national aspirations and territorial claims. India hashistorically maintained a nuanced approach to the Israel-Palestine conflict, and its position hasevolved over the years. Here are key points regarding India's role in the Israel-Palestine issue: